Sorption of Pb, Cu, Cd, and Zn by Municipal Solid Waste Composts: Metal Retention and Desorption Mechanisms. Issue 1 (18th November 2016) - Silvetti, Margherita; Demurtas, Daniela; Garau, Giovanni; Deiana, Salvatore; Castaldi, Paola
Abstract : In this study, the ability of two municipal solid waste composts to adsorb Pb, Cu, Cd, and Zn ions (Me(II)) from aqueous solutions was investigated. Sorption experiments, carried out at pH 4.5 to simulate acidic Me(II)‐polluted environments, showed for both composts higher affinity for Pb (∼0.45 mmol g −1 ) and Cu (∼0.31 mmol g −1 ) compared to Cd (∼0.25 mmol g −1 ) and Zn (∼0.10 mmol g −1 ). The sorption isotherms data fitted the Freundlich model better than the Langmuir in both composts, suggesting the presence of heterogeneous Me(II) adsorption sites. The humic acids (HA) extracted from composts contributed to 16, 23, 17, and 20% in the sorption of Pb, Cu, Cd, and Zn, respectively, while the compost water‐soluble‐fractions hardly affected the sorption/precipitation of the Me(II) (<5%). The Fourier transform infrared (FT‐IR) spectra of the different Me(II)–HA systems also indicated that the carboxylate groups of HA mainly interacted with Pb(II) and Cu(II) by forming monodentate and bidentate complexes, respectively. The sequential extraction data showed that a significant amount of Cd and Zn was retained by composts through electrostatic interactions (>65% of the respective total amounts sorbed) while most of Cu and Pb (40 and 54%) was strongly complexed and/or precipitated. The treatment of the Me(II)‐composts with citric and malic acids favored the release of >78 and 48% of Zn, 65 and 30% of Cu, and 40 and 30% of Cd, sorbed by both composts, respectively. This release was lower for Pb (<20%) as the cation more strongly retained by the organic or inorganic components of composts. Abstract : Bioavailability of trace metals (TM) in soil can be minimized through immobilization by organic amendments. The sorption capacity of two municipal solid waste (MSW) composts toward different TM, and the role of the compost water‐soluble‐fraction, humic acids, and soil/rhizosphere organic molecules, in the sorption/desorption processes are evaluated. The results suggest the suitability of MSW‐composts as immobilizing agents in TM‐polluted soils.